2019
DOI: 10.1002/ecy.2839
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluating pattern and process to understand resilience in transitional mixed conifer forests

Abstract: A key challenge to maintaining resilient landscapes is adapting to and maintaining dynamic ecological processes. In fire‐dependent ecosystems, this includes identifying and defining mechanisms through which fire influences forest structure and functionality. Interpretations of tree patterns via land survey records in the Lake States have often highlighted the importance of infrequent moderate to extreme disturbance events. However, historical survey methods are limited to observing higher severity disturbances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 92 publications
(188 reference statements)
0
10
0
Order By: Relevance
“…indicates low-to-mixed-severity fire effects at the site level during even the most extreme fire events over the past 400 yr. The more nuanced perspective we advocate for with respect to the historical fire regime of the BWCAW contributes to a growing literature that suggests a more widespread presence of surface fires in the pre-Euro-American forests of the western Great Lakes than previously thought (Drobyshev et al 2008b, Muzika et al 2015, Guyette et al 2016, Kipfmueller et al 2017, Meunier et al 2019b.…”
Section: Abundant Evidence Of Frequent Surface Firesmentioning
confidence: 88%
See 1 more Smart Citation
“…indicates low-to-mixed-severity fire effects at the site level during even the most extreme fire events over the past 400 yr. The more nuanced perspective we advocate for with respect to the historical fire regime of the BWCAW contributes to a growing literature that suggests a more widespread presence of surface fires in the pre-Euro-American forests of the western Great Lakes than previously thought (Drobyshev et al 2008b, Muzika et al 2015, Guyette et al 2016, Kipfmueller et al 2017, Meunier et al 2019b.…”
Section: Abundant Evidence Of Frequent Surface Firesmentioning
confidence: 88%
“…Critical to the restoration of fire to Great Lakes pine forests is the need to understand the historical drivers of fire occurrence in red pine forest types. Climate, fuel availability, fire exclusion, and fire suppression are often considered the primary controls on 20th-century fire occurrence in the Great Lakes Region (Heinselman 1996, Meunier et al 2019b. A diminished role of traditional Indigenous landuse as a source of frequent fire can also explain changes in fire occurrence over the last century in many places (Anderton 1999, Muzika et al 2015, Guyette et al 2016, Kipfmueller et al 2017 and has important implications for understanding the eco-cultural factors that led to the diminished presence of red pine on the landscape since Euro-American colonization (Buckman et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…, Meunier et al. ). Tree‐ring and fire‐scar records allow for increased understanding of prehistoric ecological processes that, through time, resulted in the ecological conditions (Batek et al.…”
Section: Introductionmentioning
confidence: 98%
“…The understanding of fire's importance in the ecology and management of natural communities in the eastern USA has seen continual advancement, based largely on the development of new tree-ring and fire-scar derived fire history datasets , 2011, 2018, Flatley et al 2013, Aldrich et al 2014, Kipfmueller et al 2017, Abadir et al 2019, Meunier et al 2019. Tree-ring and fire-scar records allow for increased understanding of prehistoric ecological processes that, through time, resulted in the ecological conditions (Batek et al 1999) later reported in documentary archives (Ruffner 2006, Hanberry et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Relative ratio value has the value of N:S ratio when N:S ratio is >1 and the value of S:N ratio when N:S ratio is <1 with places where closed mesic forest occurred in the southern part of the Tension Zone, whereas the narrower parts were in places with oak savanna in the south (Bolliger et al, 2004;Rhemtulla et al, 2007;Shea et al, 2014). Because differences in tree density and species composition in the eastern broadleaf forest tend to be driven by variation in fire regime, the variable pattern of ecotone width may reflect the critical role of fire as a process shaping different parts of the Tension Zone (Peterson and Reich, 2008;Meunier et al, 2019;Abrams and Nowacki, 2019). The observed patterns may also be the result of regional climate gradients, variation in topography, soils, or hydrology, or endogenous processes such as feedbacks (Curtis, 1959;Danz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%